Vascular Trauma Associated With Closed Reduction of Shoulder Dislocation: Clinical Case (Basic Health sciencies journal, 2025)
Shoulder dislocations have a high incidence in medical emergencies, with an annual incidence rate that varies between 23.1 and 23.9 per 100,000 people, which represents 1.7% of the general population, with young adults and older women being at higher risk; Among the complications associated with traumatic shoulder dislocation due to reduction, vascular and neurological injuries are included, the former being more common in elderly patients, since their blood vessels tend to be more rigid and fragile, which can affect the axillary artery or vein and its branches. This article presents the clinical case of a 59-year-old male patient with a clinical diagnosis of right shoulder dislocation secondary to a fall from his own height with subsequent reduction causing injury to the axillary artery and brachial plexus, a situation that required surgical treatment due to the extension of the mixed injury and joint involvement leading to disarticulation of the affected upper limb.
Keywords: Surgical amputation; Shoulder dislocation; Closed reduction; Brachial plexus; Axillary artery